Nanocomplexes Based on Amphiphilic Hyaluronic Acid Derivative and Polyethylene Glycol–Lipid for Ginsenoside Rg3 Delivery. Issue 10 (11th August 2014) - Lee, Jae‐Young; Yang, Heejung; Yoon, In‐Soo; Kim, Sang‐Bum; Ko, Seung‐Hak; Shim, Jae‐Seong; Sung, Sang Hyun; Cho, Hyun‐Jong; Kim, Dae‐Duk
<x xml:space="preserve">Abstract</x> Hybrid nanocomplex formulations, based on amphiphilic hyaluronic acid–ceramide (HACE) and lipids, were fabricated for the delivery of 20(S)‐ginsenoside Rg 3 [(S)‐Rg3]. Nanocomplexes with less than 200 nm mean diameter, narrow size distribution, spherical shape, and negative zeta potential were prepared. The maintenance of the structural stability of the hybrid nanocomplexes in the blood stream was demonstrated by measuring their particle size in serum. Nanocomplexes based on HACE, phosphatidylcholine (PC), and 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐N‐[methoxy(polyethyleneglycol)‐2000] (DSPE‐PEG) showed a sustained drug release profile compared with other formulations. Blank nanocomplexes exhibited negligible cytotoxicity within the tested concentration range in A549 human lung adenocarcinoma cells. The cellular uptake efficiency of hybrid nanocomplexes was improved compared with the HACE‐based nanoparticles probably because of interactions between lipids and the cellular membrane. The results of a pharmacokinetic study in rats revealed decreased in vivo clearance of (S)‐Rg3, especially in the HACE/PC/DSPE‐PEG‐based hybrid nanocomplex (F3) group. The hybrid nanostructure and the outer PEG chain likely contributed to improve in vivo performance of the F3 group. Thus, these developed hybrid nanocomplexes could serve as good candidates for tumor‐targeted delivery of anticancer agents. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3254–3262, 2014